Perencanaan Persediaan Packaging dengan Menggunakan Analisis Always Better Control (ABC) dan Metode Min-Max Pada PT. TR - Kartika, Riza Adinda Nararia; Arifin, Jauhari (Industrika : Jurnal Ilmiah Teknik Industri, 2024)
This research aims to update min-max stock and focus on which items need extra supervision using ABC analysis at PT TR. This data collection technique uses observations and statistical data sets. Data collection methods such as direct observation of work areas aim to collect actual data needed for this research. The statistical data set was obtained from the PPIC department. The data source in this research is secondary data, where the data was obtained from data collectors indirectly with the PPIC department. The results of this research indicate that the standards for determining and managing raw material inventories are in accordance with the standards set by the company. The researcher concluded that by using min-max, PT TR can obtain alternative minimum and maximum limit orders according to the budget requirements spent in ordering raw materials, but there are still weaknesses in packaging inventory management activities. Companies such as PT TR must focus more on Products included in group A for the packaging procurement process because this group has a large percentage of monetary value and requires extra supervision. Keywords: ABC Analysis, Inventory, Min-Max Stock, Warehouse